Mesoporous Manganese Oxide Catalyzed Aerobic Oxidative Coupling of Anilines To Aromatic Azo Compounds. (8th January 2016) - Dutta, Biswanath; Biswas, Sourav; Sharma, Vinit; Savage, Nancy Ortins; Alpay, S. Pamir; Suib, Steven L.
Abstract: Herein we introduce an environmentally friendly approach to the synthesis of symmetrical and asymmetrical aromatic azo compounds by using air as the sole oxidant under mild reaction conditions in the presence of cost‐effective and reusable mesoporous manganese oxide materials.